Antihipercolesterolemia Effects and Acute Toxicity Test of Pheophytin on Green Tea - Lia Kusmita; Ika Puspitaningrum (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Hypercholesterolemia is a condition characterized by increased levels of total cholesterol in the blood. Pheophytin is the result of degradation of chlorophyll which is the dominant pigment in green tea, and has been shown to have the same antioxidant properties as ?- carotene. This study aims to determine the antihypercholesterolemia effect and effective dose of pheophytin isolates and acute toxicity tests to determine the safety level of pheophytin isolates. Antihipocolesterolemia test uses induction of high-fat feed that is a mixture of standard food, pork oil and quail egg yolk (16: 3: 1). While the acute toxicity test is carried out based on OECD 423, Clinical symptoms that arise for 3 hours are observed intensively. Histopathological examination data of liver and kidney organs were performed on day 14. Data obtained in the form of LD 50 and clinical symptoms that arise as well as histopathological results were analyzed qualitatively. Statistical test results of percent reduction in total cholesterol levels showed a significant difference between the negative control group and the pheophytin isolates of the three doses. This proves that pheophytin isolates can have antihypercholesterolemic effect with an effective dose of 10 mg/kgBW. Histopathological examination results of aorta and liver of rats showed that the higher the dose of pheophytin isolates, the lighter the degree of fatty acid. While the toxicity test results showed that the LD50 value of pheophytin isolates was more than 2000 mg / kgBW (non-toxic category). However, pheophytin isolate with LD50 is more than 2000 mg/kgBW which has shown the presence of pancreatic degeneration and hydropic degeneration, but necrosis has not occurred yet.